Seasonal variation in foraging conditions for Ring Ouzels Turdus torquatus in upland habitats and their effects on juvenile habitat selection. (22nd October 2012) - Sim, Innes M. W.; Ludwig, Sonja C.; Grant, Murray C.; Loughrey, Joanna L.; Rebecca, Graham W.; Redpath, Steve
Abstract : Recent studies indicate that variation in juvenile survival may be particularly important in driving avian population dynamics. The quality of habitats available to inexperienced juveniles of migrant species is critical to their survival because they must obtain enough food to build up fat reserves for migration, while avoiding predation. We radiotracked 110 juvenile Ring Ouzels Turdus torquatus, a species of high conservation concern in the UK, to quantify for the first time seasonal patterns in foraging habitat and food abundance during this potentially key life‐history period. Key attributes of foraging plots were compared with those on control plots (representing the broad habitat types selected by foraging juveniles) during 2007–08. Birds foraged on invertebrates in grass‐rich plots during June to mid‐July and then shifted to foraging mainly on moorland berries in higher‐altitude, heather‐rich plots during mid‐July to early‐September. Juveniles selected invertebrate foraging plots with low soil acidity, and increasingly selected plots with high earthworm (an important food) biomass and grass cover, but low grass and all vegetation height as the season progressed. In contrast, earthworm biomass and grass cover remained constant, and grass and all vegetation height increased, on control plots. Juveniles selected berry foraging plots with higher abundance of ripe Bilberries Vaccinium myrtillus and Crowberries Empetrum nigrum than found on control plots. Juvenile Ring Ouzels thus appear to require access to short, grass‐ and invertebrate‐rich habitat during early summer, and taller, heather‐dominated and berry‐rich areas in late summer. The use of two distinct habitat types during the pre‐migratory period illustrates the need for a detailed understanding of the requirements of juvenile birds.